0197 The Relationship between Sleep and Occupationally-Relevant Outcomes in Elite Us Army Soldiers. (12th April 2019) - Bessey, Alexxa F; Chabuz, Richard H; Mantua, Janna; Capaldi, Vincent F; Sowden, Walter J
Abstract: Introduction: Although previous studies have highlighted the important role of sleep within occupational settings, few studies have examined the role of sleep on occupational outcomes in high-risk organizations (HRO), where mistakes and errors can have grave consequences. Therefore, the current study examined the relationship between self-reported sleep and occupational outcome measures in a high-risk military training environment. Methods: Cross-sectional survey data were collected from eighteen male U.S. soldiers (28-43 years) within an elite US Army unit. Measures included Insomnia Severity Index (ISI), Fatigue Severity Scale (FSS), Pittsburgh Sleep Quality Index (PSQI), and Emotional Exhaustion Scale from the Maslach Burnout Inventory. The relationship between subjective sleep and occupational outcomes was tested using correlations. Poorer sleep quality was predicted to be related to poorer occupational outcomes. Results: As predicted, the ISI was significantly correlated with the FSS (r=.489; p=.039) and the Emotional Exhaustion scale (r=.525; p=.025), such that poorer sleep quality was linked with higher fatigue and emotional exhaustion. Interestingly, fatigue and emotional exhaustion were strongly correlated with the functional constructs within the ISI, which describe impairments due to sleep loss (FSS [r=.573; p=.010; Emotional Exhaustion Scale [r=.662; p=.002]), but not the sleep quality-related items, which query specific sleep difficulties (p-values>.73). Although the global score of PSQI was not correlated with the FSS or Emotional Exhaustion scale (p-values>.21), Component 7 (PSQI functional constructs) was significantly correlated to the FSS and Emotional Exhaustion Scale (FSS [r=.570; p=.011; Emotional Exhaustion Scale [r=.561; p=.013]) such that poorer sleep was related to poorer outcomes. Conclusion: The current study established the important relationship between subjective sleep quality and occupational outcomes. Furthermore, the diverging links between constructs in the ISI/PSQI and occupational outcomes indicate that this population may not have "typical" sleep difficulties (e.g., insomnia) but still feel poor sleep quality is impacting their daily functioning. This is relevant for research methodology within HROs since assessing sleep using traditional measures may fail to parse apart nuances within these unique occupational environments. Support (If Any): Department of Defense Military Operational Medicine Research Program (MOMRP).